2007
DOI: 10.1080/02688690701466313
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysm and arachnoid cyst: a rare association between two cerebral malformations

Abstract: Intracranial aneurysms and arachnoid cysts are cerebral disorders of a high prevalence. However, association between both malformations is a rare finding. The aim was to analyse this association with regard to the different clinical presentations according to the haemorrhage types, as well as the pathogenesis of this association. We searched the English language literature in MEDLINE database in order to include all manuscripts in which this association was found. A new case of a 55-year-old man with a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In most of these cases, intracranial hemorrhage was the first manifestation. 5 There has also been one report of multiple aneurysms associated with arachnoid cysts, 2 which evolved with rupture of the intracystic aneurysm, without typical subarachnoid hemorrhage. 1 All of these possibilities should be borne in mind during neuroimaging evaluations on patients with arachnoid cysts without symptoms and on those who present with intracranial hemorrhage.…”
Section: Case Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…In most of these cases, intracranial hemorrhage was the first manifestation. 5 There has also been one report of multiple aneurysms associated with arachnoid cysts, 2 which evolved with rupture of the intracystic aneurysm, without typical subarachnoid hemorrhage. 1 All of these possibilities should be borne in mind during neuroimaging evaluations on patients with arachnoid cysts without symptoms and on those who present with intracranial hemorrhage.…”
Section: Case Reportmentioning
confidence: 99%
“…2 In the present report, this diagnosis was an incidental finding. de Oliveira et al 5 found associations between aneurysms and arachnoid cysts through a review of the literature in which only 10 cases were reported. In most of these cases, intracranial hemorrhage was the first manifestation.…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations